REPEATED GIVING OF CASH WAQF: A CASE STUDY OF SABAH, MALAYSIA - Nurul Izzati Binti Justine; Mohamad Isa Abd Jalil (Bank Indonesia, 2022)
This study examines repeated waqf contributions in Sabah State, Malaysia. Religious obligation, benevolence, and familiarity with and trust in the waqf institution are the variables that are expected to have a positive relationship with the repeated behaviour of giving waqf cash. These antecedents are drawn from previous empirical studies. A total of 200 respondents who have repeatedly contributed to cash waqf shared their opinions through a survey form distributed by using the